2016
DOI: 10.1016/j.jbusres.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Logic combination and performance across occupational communities: The case of French film directors

Abstract: This article analyzes the effects of logic combination on cultural entrepreneurs' performance in both their original (artistic) and new (business) occupational communities. An analysis of the impact of the director-producer logic combination on artistic and commercial performance in French cinema confirms an asymmetry in outcomes: (1) although performance in the original artistic community is impaired by repeated logic combination (receiving less awards), (2) performance in the new business community benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Studies of this nature focus on the histories of the participants (Cattani et al, 2013;Jung & Kim, 2010;Kim, 2013;Narayan & Kadiyali, 2016;Rossman et al, 2010) and also the networks they operate within (Ebbers & Wijnberg, 2009;Packard et al, 2016;Yudelson, 2011), as well as issues of discrimination within such networks (Grugulis & Stoyanova, 2012). Against this backdrop, both commercial and artistic outcomes are examined by Hadida (2010Hadida ( , 2013, and Durand and Hadida (2016). Relatedly, the career paths of film directors and their impacts on box office outcomes are studied by John et al (2017), Chan et al (2018), and Jensen and Kim (2020).…”
Section: Stars and Talentmentioning
confidence: 99%
“…Studies of this nature focus on the histories of the participants (Cattani et al, 2013;Jung & Kim, 2010;Kim, 2013;Narayan & Kadiyali, 2016;Rossman et al, 2010) and also the networks they operate within (Ebbers & Wijnberg, 2009;Packard et al, 2016;Yudelson, 2011), as well as issues of discrimination within such networks (Grugulis & Stoyanova, 2012). Against this backdrop, both commercial and artistic outcomes are examined by Hadida (2010Hadida ( , 2013, and Durand and Hadida (2016). Relatedly, the career paths of film directors and their impacts on box office outcomes are studied by John et al (2017), Chan et al (2018), and Jensen and Kim (2020).…”
Section: Stars and Talentmentioning
confidence: 99%
“…35 An extreme version of scenario 3 may see the disappearance of movie theatres, and the replacement of what would become outdated film festivals and film awards with new status markers and more encompassing selection systems incorporating feature films and episodic shows. In a more conservative convenience logic dominant scenario, online streaming services would still engage in a few theatrical releases, perceived as prerequisites to creating or signalling status markers and to gaining industry prestige (Durand and Hadida 2016;Webster and Hysom 1998). Both Amazon Studios and Netflix have experimented with theatrical release, and both have mostly done so to create awareness for their movies, to qualify for awards, and to court filmmakers whose preferred release channel remains the big screen.…”
Section: Convenience Logic Dominantmentioning
confidence: 99%
“…Yet, different audiences also adhere to different valuation criteria which may pose challenges to audience diversification. Ertug et al (2016) showed that museums and galleries use different yardsticks for gauging an artist's reputation, and Durand and Hadida (2015) suggested that occupational communities punish actors for deviating from their canon of expectations. Shymko and Roulet (2017) found that artistic organizations are penalized by their peers if they seek recognition from corporate actors because they are seen to violate the norms inherent in the artistic logic.…”
Section: Social Valuationmentioning
confidence: 99%